2006
DOI: 10.1128/mcb.00580-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcription Factor NFAT in Glucose and Insulin Homeostasis

Abstract: Compromised immunoregulation contributes to obesity and complications in metabolic pathogenesis. Here, we demonstrate that the nuclear factor of activated T cell (NFAT) group of transcription factors contributes to glucose and insulin homeostasis. Expression of two members of the NFAT family (NFATc2 and NFATc4) is induced upon adipogenesis and in obese mice. Mice with the Nfatc2 ؊/؊ Nfatc4 ؊/؊ compound disruption exhibit defects in fat accumulation and are lean. Nfatc2 ؊/؊ Nfatc4 ؊/؊ mice are also protected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 66 publications
4
74
0
1
Order By: Relevance
“…Indeed, the global deletion of NFATc2 in mice has been shown to increase the expression of chondrocytic-specific genes and chondrogenesis, suggesting that NFATc2 is a negative regulator of chondrocyte growth and differentiation (37). Global NFATc2/c4 double knock-out mice exhibit defects in fat accumulation and reduced adiposity, suggesting that NFAT signaling is positive regulator of adipogenesis (38). Finally, it has been shown that the number of primary myofibers and muscle size are decreased in the global NFATc3-deficient mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the global deletion of NFATc2 in mice has been shown to increase the expression of chondrocytic-specific genes and chondrogenesis, suggesting that NFATc2 is a negative regulator of chondrocyte growth and differentiation (37). Global NFATc2/c4 double knock-out mice exhibit defects in fat accumulation and reduced adiposity, suggesting that NFAT signaling is positive regulator of adipogenesis (38). Finally, it has been shown that the number of primary myofibers and muscle size are decreased in the global NFATc3-deficient mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…There are four calcium responsive NFAT isoforms and all are expressed in 3T3-L1 adipocytes, with NFATc1 and -c3 constitutively expressed and NFATc2 and -c4 induced during adipocyte differentiation (55). Despite similar expression of the FLAG-tagged NFAT proteins, only NFATc2 and -c4 showed significant levels of interaction with lipin 1 (Fig.…”
Section: Lipin 1 Interacts With Nfatc4mentioning
confidence: 99%
“…NFATc2 and NFATc4 have also been implicated in both adipocyte differentiation and expression of adipokines. Mice deficient for both NFATc2 and NFATc4 have decreased production of resistin in adipose tissue and are resistant to diet-induced obesity (55). The role of lipin 1 in triacylglycerol synthesis, when combined with its ability to modulate the activity of a transcription factor that regulates expression of cytokines and adipokines, positions lipin 1 as a potential regulator of the negative consequences of increased triacylglycerol deposition in adipocytes.…”
mentioning
confidence: 99%
“…Moreover, these mice do not accumulate fat. These findings could arise from changes in adipokine signaling, because NFAT also seems responsible for the production of resistin, a protein that confers insulin resistance (43 ). During the last few years, several genes predisposing to posttransplantation diabetes mellitus have been discovered (44 ).…”
Section: Brainmentioning
confidence: 99%